Robot Manipulator Pelontar Bola Pingpong Berbasis APP Inventor Dan Bluetooth - Andi Hasad; Ali Musaffa; Abdul Hafid Paronda; Muhammad Amin Bakri (Sekolah Tinggi Teknik - PLN, 2020)
Ping pong ball throwers are used as automatic ball shooters as a method of self-training and training the skills of professional athletes. By adding wireless communication, ping pong ball throwers can be controlled remotely. The controller interface is created using the App Inventor so that controllers can be carried out via smart phones. To get the ball throwing “service” required a combination of parameter values of the speed of the ejection motor and the angle of the servo motor.